Host Defense Mechanisms in the Male Genital Tract: Role of Innate Immunity - KULKARNI, B A (The Indian Journal of Animal Reproduction, 2023)
Innate immunity is the first defence to infection. The submucosa of male genital tract is rich in lymphocytes,1eutroph ils, macrophages, and lymphatic tissue, which on microbial invasion produce antimicrobial peptidesand proteins viz., defensins. cathelicidins, lactoferrin, lysozyme and various other proteins. Innate immunity is quick responsive to microbial invasion, controls the infection in the, early period of exposure to pathogenic,nicroorganisms and is phylogenetically ancient than adaptive immune system. The innate imm'une system is wellequipped with cellular and molecular armaments for immediate protective response against the invasion of.pathogenic microorganisms. The cellular components are lymphocytes, monocytes, neutrophils, macrophagesand natural killer (NK) cells. The molecular components include mucins, defensins. cathelicidins, proteaseinhibitors, serpins, lysozyme, a-macroglobulin. cystatins, Toll~like receptors (TLRs), lactoferrin, _interieukins, complement system, bactericidal/permeability increasing protein (BPI), lipopolysaccharide binding protein (LBP), nitric oxide (NO), hydrogen peroxide (Hp2) and collectins. Recent studies have demonst_rated the' expressi?nand localization of various peptides and proteins having antimicrobial activity against a broad spectrum of bacteria, viruses and fungi in the male genital tract. These antimicrobial peptides and proteins. with their host defense mechanisms in the male genital tract are discussed briefly in this review.
Keywords: Innate Immunity; Defensins; Cathelicidins; Protease Inhibitor; Host defense proteins